English Language Education Student-Teachers’ Perception on TPACK - Wijaya, I Nyoman Arga; Ratminingsih, Ni Made; Dewi, Ni Luh Putu Eka Sulistia (STKIP AGAMA HINDU SINGARAJA, 2022)
Technological advances in the 21st century have had a major influence on the development of education today. The integration of technology into the classroom affects the learning process as well as the way teachers implement and develop learning activities in the classroom. This study aims to find out about the perception of student-teachers towards Technological Pedagogical Content Knowledge (TPACK). This study uses a quantitative design to determine student-teacher perceptions of the TPACK framework. Survey was conducted to view and collect data using questionnaires, the participants were given the questionnaire, which contains five Likert scale scales to gain the data and TPACK of the student teachers. The subjects of this research are 141 participants of 2017-years students-teachers of ELE in Ganesha University of Education, Singaraja, Bali. The result showed that the student-teachers have a positive perception toward the implementation of TPACK in the teaching process.